PERAN MINAT INVESTASI DALAM MEMEDIASI PENGETAHUAN INVESTASI, MOTIVASI INVESTASI, DAN MODAL MINIMAL INVESTASI TERHADAP KEPUTUSAN INVESTASI (Studi Kasus Investor Pada BEI Berdomisili Kota Pekalongan): Dibuat oleh Alliyatul Himmah, Sobrotul Imtikhanah, Rini Hidayah (Prodi Akuntansi FEB Universitas Muhammadiyah Pekajangan Pekalongan) - Alliyatul Himmah; Sobrotul Imtikhanah; Rini Hidayah (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
This study aims to analyze the role an investment intersest in mediating the investment knowledge, the investment motivation, and minimum investment capital on investment decisions. It used a survey and questionnaire to collect the data with using a proportionate stratified random sampling with Slovin formula. A hundred respondents as the investor of Indonesian Stock Exchange located in Pekalongan were taken as the sample. Meanwhile, it used a multiple linear regression and a path analysis for the data analysis technique. Partially the results shows the investment knowledge, the investment motivation, and minimum investment capital have a significantly affected on the investment decisions. Furthermore, from the path test, it shows the investment interest has significantly mediated the investment knowledge, the investment motivation, and a minimum investment capital on the investment decisions. Keywords: the investment knowledge, the investment motivation, a minimum investment capital, the investment decisions